2011
DOI: 10.1016/j.jaapos.2011.01.106
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal reproducibility of optical coherence tomography measurements in children

Abstract: Purpose-To evaluate the longitudinal reproducibility of optical coherence tomography (OCT) measurements in normal and glaucomatous eyes of children.Methods-In this two-setting prospective study, OCT-3 was used to obtain fast retinal nerve fiber layer (RNFL) and of macular thickness scans. In the first study setting, the normal eyes of healthy children were scanned on presentation, at 2 weeks, and 3 years, with axial length measured at the first and last examinations. In the second setting, OCT scans of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
(21 reference statements)
3
12
0
Order By: Relevance
“…9,11,12 Prakalapakorn and colleagues performed one of the only longitudinal studies of circumpapillary RNFL thickness in children with glaucoma using time-domain OCT, which demonstrated CVs somewhat comparable to our study. 29 While our results can be used to plan future handheld OCT studies in children with optic pathway gliomas, our results may not be applicable to children with other optic neuropathies (i.e., glaucoma, optic neuritis), as their pattern of RNFL loss and mechanism of damage are different.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…9,11,12 Prakalapakorn and colleagues performed one of the only longitudinal studies of circumpapillary RNFL thickness in children with glaucoma using time-domain OCT, which demonstrated CVs somewhat comparable to our study. 29 While our results can be used to plan future handheld OCT studies in children with optic pathway gliomas, our results may not be applicable to children with other optic neuropathies (i.e., glaucoma, optic neuritis), as their pattern of RNFL loss and mechanism of damage are different.…”
Section: Discussionmentioning
confidence: 92%
“…29 The ophthalmologic monitoring and neuro-oncologic care of children with optic pathway gliomas, especially those with NF1-related optic pathway gliomas, is challenging for a number of reasons. First, since optic pathway gliomas typically occur in toddlers and very young children, a group known to have a low rate of success in completing recognition VA testing 30 and manual/automated perimetry, circumpapillary RNFL thickness could serve as a surrogate marker of pregeniculate visual pathway integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The OCT technique 12,17,26 and its reproducibility in children 27,28 have already been described in several reports. An optic disc cube 200 Â 200 protocol was used to obtain the RNFL thickness and ONH measurements.…”
Section: Optical Coherence Tomography (Cirrus Hd-oct) Measurementsmentioning
confidence: 99%
“…We know that normative values for these OCT parameters vary with age, race and axial length 10. Reproducibility studies are scarce11 12 and we still do not know the longitudinal reproducibility of spectral domain OCT values in a growing child 11 12…”
mentioning
confidence: 99%
“…Second, given that OCT values correlate with axial length, we expect that the longitudinal reproducibility of OCT in the eyes of growing children would be affected by axial growth. One study found that the difference that would be engendered by axial length growth in a growing child is negligible since it would be less than the test–retest variance of the time domain OCT machine 12. However, SD-OCT has been reported to have better reproducibility than time domain OCT in both adults and children,11 so one would expect that a change in axial length will affect SD OCT values.…”
mentioning
confidence: 99%